Evolution of antibody titres against Epstein–Barr virus and human herpesvirus 6A/B and expression of multiple sclerosis-associated retrovirus in the serum of pregnant multiple sclerosis patients - Silvia Pérez-Pérez (Nature Portfolio, 2021)
Abstract Epstein–Barr virus (EBV), human herpesvirus 6A/B (HHV-6A/B) and multiple sclerosis (MS)-associated retrovirus (MSRV) have been described as possible MS triggers. We analysed antibody titres against EBV and HHV-6, and MSRV envelope (env) mRNA expression, in the serum of pregnant multiple sclerosis patients (P-MS) to study their possible link to the clinical activity of MS during pregnancy and postpartum and their possible role as relapse predictors. For that purpose, serum samples were collected from 71 pregnant women (50 pregnant MS and 21 pregnant healthy controls—P-HC) during pregnancy and postpartum. Relating to antibody titres, IgM antibody titres against HHV-6A/B were significantly higher in P-MS than in P-HC both in each pregnancy trimester and in the postpartum period. Moreover, IgM antibody titres against HHV-6A/B were higher in P-MS who suffered a relapse during the postpartum. Regarding MSRV env mRNA expression, the prevalence in the first trimester of pregnancy was significantly higher in P-MS who suffered relapses during pregnancy. Summing it up, high IgM antibody titres against HHV-6A/B and MSRV env mRNA expression during the first trimester of pregnancy could act as relapse predictors for the gestation/postpartum periods.